Formal Description of Some Linguistic Phenomena in Croatian by Lexical-Functional Grammar (LFG) - Seljan, Sanja (Array, 2002)
Lexical-Functional Grammar (LFG) supports several distinct but interrelated levels of analysis: lexical level, constituent, argument and functional structures that integrate morphological, lexical, syntactic and semantic information. Linguistic phenomena are analyzed by grammatical functions presented in the lexicon and integrated in functional structure, after which this grammar has been named. Belonging to the group of context-sensitive grammars, LFG is supposed to describe words in context. As the main idea of this grammar is to use grammatical functions that exist in natural languages, it is tends to be suitable for description of highly structured languages and for languages with free word order. LFG is generative non-transformational grammar that integrates knowledge from informatics, linguistics and logic. Although it uses two main levels of representation, functional( f-) structure that tends to be universal across the languages when describing one linguistic phenomena and constituent ( c-)structure that is specific for the language, other levels are also mentioned, such as lexical analysis and argument structure. LFG has been used until now for text analysis, text generation and machine translation. Since the Croatian language has relatively free word order and rich morphological system, one of the central questions is case-marking and formal description of agreement. I propose that the Croatian morphology has a recursive binary structure, which allows association of the first part of the word, which is marked as word category and, possibly marked with semantic constraints, with last part, i.e. with paradigmatic endings. Sentences are generated by syntactic rules, passing after that through semantic constraints marked in the rules or/and the lexical units. The possibility of decomposing into binary features enables adding of new constraints or introducing contextual elements, which is important characteristic of contextual formal grammars. The theoretical formal descriptions for the Croatian language is tested on the Avery Andrew’ s LFGW model, developed at University of Brisbane.